Influence of Stresses Ina Modified Non-Metallic Spur Gear Pair - Manikandan, J.; Murali, Bala (International Journal of Psychosocial Rehabilitation, 2019)
A gear is a rotating machine part having cut teeth, or cogs, which mesh with another toothed part in order to transmit torque. In order to avoid undercutting and interference, addendum modification of the gear tooth is carried out in this paper, a standard and a profile corrected carried out spur gear pair is modeled. The material used is plastic (Nylon-66).The gear ratio assumed was 1.5 with a module of 10 and correction factor taken to be 0.5. The dimension of the models was arrived at by theoretical calculations. In this paper, a model part is done with PRO-E for the modeling of the spur gear for both standard and profile corrected tooth. The finite element model of the gear tooth is imported to an analysis software ANSYS to study the bending effects for different modules. Results were obtained from the comparisons made for the bending stress variations for both the standard plastic spur gear tooth and the profile corrected plastic spur gear. The results of the study for the addendum modified tooth showed a decrease in bending stresses for the wider tooth for the same loading